Targeted metagenomics identification of microbiome in preschools exposed to air pollutants and their association with respiratory health symptom, allergy and eczema - Onwusereaka, Cynthia Oluchi; Jalaludin, Juliana; Mohd Isa, Khairul Nizam; Amin Nordin, Syafinaz; Abubakar, Suhaili; Choo, Veronica Chua Poo (Springer Science and Business Media, 2024)
Microorganisms are an important aspect of the environment which have significant effects on human health. Children are more vulnerable to the effects of microbial pollutants, pathogens and allergens. Microbial components of indoor air cannot be overemphasized due to its vastness and ubiquitous nature. This is a cross sectional comparative study which analysed microbiome in 10 preschools according to their level of exposure to outdoor air pollutant sources using amplicon sequencing technique. A total of 20 dust samples were collected from indoor and outdoor environment and analysed for the presence of bacteria and fungi. A detailed questionnaire was used to assess the respiratory health status of the respondents. Indoor air quality was assessed by measuring the level of particulate matter (PM2.5 and PM10), temperature, relative humidity, air velocity, and CO2. Exposed area recorded higher level of PM10 and CO2 (p <0.05) while temperature, relative humidity and air velocity were higher in the comparative area (p <0.05). Health symptoms were significantly higher in exposed area for cough, eczema and allergy symptoms (p <0.05). Predominant bacteria species includes Acinetobacter_radioresistens, Acinetobacter_seifertii, Lactobaccillus_iners, Pseudomonas_B_luteola, and Franconibacter_pulveris while predominant fungi species includes Rhodosporidioboluc_fluvialis, Rhodotorula_kratochvilovae, Aspergillus_penicilloides, Aspergillus_gracilis, Curvularia_sorghina, Eupenidiella_venezuelensis, Rhodosporidiobolus_ruineniae, Bipolaris_papendorfii and Curvularia_lunata. Cough symptom was strongly associated with PM10 (AOR =1.27), carpeting (AOR =1.62), Cladosporium dominicanum (AOR =2.12) and Aureobasidium gracilis (AOR =2.04). Eczema was strongly associated with keeping furry pet (AOR =5.46) and Rhodotorula_toruloides (1.02). Allergy was strongly associated with PM10 (AOR =3.23), Megasporoporia_bannaensis (AOR =1.43) and Malassezia_restricta (AOR =2.10). Preschools located close to outdoor air pollutants were more exposed to pollutants and microbiome from indoor and outdoor sources. Health symptoms were significantly associated with air pollutants, therefore proper measures should be implemented to mitigate the exposure to microbiome, infiltration of outdoor air pollutants and health effects on children.